Molecular mechanisms in the first step of ABA-mediated response in Coffea ssp - Cotta, Michelle Guitton (2016)
Abscisic acid (ABA) is a phytohormone universally conserved in land plants which coordinates several aspects of the plant response to water deficit such as root architecture, seed dormancy and regulation of stomatal closure. A mechanism of ABA signal transduction has been proposed, evolving intracellular ABA receptors (PYR/PYL/RCARs) interacting with PP2Cs phosphatases and SnRK2 protein kinases. The goal of this study was to identify and characterize for the first time the orthologs genes of this tripartite system in Coffea. For this purpose, protein sequences from Arabidopsis, citrus, rice, grape, tomato and potato were chosen as query to search orthologous genes in the Coffee Genome Hub (http://coffee-genome.org/). Differential expression in tissues as leaves, seeds, roots and floral organs was checked through in silico analyses. In vivo gene expression analyses were also performed by RT-qPCR in leaves and roots of drought-tolerant (DT 14, 73 and 120) and drought-susceptible (DS 22) C. canephora Conilon clones submitted (or not) to drought. The expression profiles of the tripartite system CcPYL-PP2C-SnRK2 genes were also analyzed in leaves of C. arabica (Ca) and C. canephora (Cc) plants grown under hydroponic condition and submitted to ABA exogenous treatment (500 µM). This approach allowed the identification and characterization of 24 candidate genes (9 PYL/RCARs, 6 PP2Cs and 9 SnRK2s) in Cc genome. The protein motifs identified in predict coffee sequences enabled characterize these genes as family’s members of PYL/RCARs receptors, PP2Cs phosphatases or SnRK2 kinases of the ABA-dependent response pathway. These families were functionally annotated in the Cc genome. In vivo analyses revealed that eight genes were up-regulated under drought conditions in both leaves and roots tissues. Among them, three genes coding phosphatases were expressed in all (DT and DS) clones therefore suggesting that they were activated as a general response to cope with drought stress. However, two other phosphatase coding genes were upregulated only in the DT clones, suggesting that they constitute key-genes for drought tolerance in these clones. The DT clones also showed differential gene expression profiles for five other genes thus reinforcing the idea that multiple biological mechanisms are involved in drought tolerance in Cc. In response to exogenous ABA, 17 genes were expressed in leaves of Cc and Ca plants. Several genes were differentially expressed in the DT clone 14 either in control condition or after 24h with ABA treatment. Under control condition, five genes were higher expressed as in the Cc as in Ca DT plants. The kinase CcSnRK2.6 was highlighted as gene specifically expressed in the Cc plants (DT and DS) after 72h of ABA treatment. Overall, it was observed that ABA signaling pathway is delayed in the DS C. arabica Rubi. Those molecular evidences corroborated with microscopies analyses which showed that the DT clone 14 was more efficient to control the stomatal closure than other coffee plants in response to ABA treatment. All these evidences will help us to identify the genetic determinism of drought tolerance through ABA pathway essential to obtain molecular markers that could be used in coffee breeding programs.